Financial Literacy sebagai Mediator pada Hubungan Personality dan Locus of Control dengan Financial Management Behavior Generasi Millennials - Devi Maharani Tanusaputri; Honey Wahyuni Sugiharto Elgeka; Anton Johannes Tjahjoanggoro (Universitas Muhammadiyah Jember, 2022)
Currently, the millennial generation is in a productive period at work and making money. However, nowadays, it is found that several generations of millennials have difficulty managing their finances. This study aims to examine the role of financial literacy mediators in the relationship between conscientiousness, neuroticism, and external locus of control with financial management behavior in Indonesia's millennials generation. This study used a correlational quantitative survey approach with a total of 166 respondents. The snowball sampling technique was used for sampling, and the data analysis technique used the Hayes Process Model 4. This study found the role of financial literacy as a mediator only in the relationship between neuroticism and external locus of control with financial management behavior. The awareness of the government and millennials generation on the importance of financial knowledge should be increased, mostly related to financial knowledge, to produce better and responsible financial management.